HUBUNGAN POLA KONSUMSI PANGAN DENGAN TINGKAT KOLESTEROL DARAH TOTAL PADA PEGAWAI NEGERI SIPIL DI KANWIL DIREKTORAT JENDRAL PERBENDAHARAAN PROVINSI SUMATERA UTARA KOTA MEDAN TAHUN 2013 - Siska Marina Damanik; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Currently, Indonesia is facing double nutritional problems, namely lack of nutrition and over nutrition. Over nutrition is considered as the early signal of the coming of degeneratif disease such as Coronary Heart Disease. The attempt efforts to overcome and to prevent Coronary Heart Disease is by regulating food consumption pattern especially by controlling the fat supplied by the food consumed. The purpose of this study was to find out the between the food consumption patternand the level of total blood cholesterol in Civil Servants in the regional Office of Directorate General of Treasury, the Province of Sumatera Utara, Medan with cross-sectional design. The primary data for this study were obtained by distributing questionaires containing food consumption, characteristic, total blood cholesterol, measurement of Civil Servants. The secondary data were obtained from general description of the regional Office of Directorate General of Treasury, the Province of Sumatera Utara, Medan. The correlation between the food consumption pattern and the level of cholesterol was descriptively analyzed through Exact-Fisher statistic test at α = 0.05. The result of this study showed that most of the Civil servants often consumed aminal food (1-3 times a week) such as eggs, chicken, beef/mutton, ampele, shrimp/squid/crab and other food containing fat such as fried and coconut-milk contained food. The average total blood cholesterol was 120.8 mg/dl, most of the energy consumed by the Civil Servants was good (80%) and there was no correlation between energy consumption and the level of total blood cholesterol (p=0.768). fat energy consumption was higher (75%), therefore, there was a significant correlation between fat energy consumption and the level of total blood cholesterol (p=0.001), between saturated fatty acid intake and the level of blood cholesterol (p=0.002), and between unsaturated fatty acid intake and the level of total blood cholesterol (p=0.001). The Civil Servants are suggested to control their consumption pattern by reducing to consumed fat and controling the frequncy or eating fat and cholesterol containing food. Keywords : Food Consumption Patterns, Total Blood Cholesterol Level, Civil Servant